Reform of Sexual Crimes in the National Criminal Code: Perspectives on Restorative Justice and Victim Protection - Ade Ari Gumilar; Iwan Rasiwan; Sri Setiawati; Johannes Triestanto; Halisma Amili (CV. AFDIFAL MAJU BERKAH, 2026)
The enactment of the new Indonesian Criminal Code (KUHP) represents a significant milestone in the reform of national criminal law, particularly in addressing sexual offenses. This reform is not only reflected in the expansion of offense definitions and the recalibration of criminal sanctions, but also in the formal recognition of restorative justice approaches and the strengthening of victim-centered protection mechanisms. This article aims to examine the extent to which restorative justice principles are incorporated within the new Criminal Code and to assess their implications for the fulfillment of victims’ rights in cases of sexual crimes. The study employs a normative legal research method, utilizing statutory and conceptual approaches through an analysis of the new Criminal Code, the Law on Sexual Violence Crimes, as well as relevant legal literature and national academic journals. The findings indicate that, at the normative level, the new Criminal Code provides legal space for the application of restorative justice as an alternative mechanism for resolving criminal cases, including certain categories of sexual offenses. Nevertheless, the implementation of this approach continues to face substantial challenges, particularly the risk of victim marginalization, power imbalances between offenders and victims, and the inadequacy of restitution and recovery mechanisms. Consequently, more explicit regulatory frameworks, clear implementation guidelines, and a stronger victim-oriented perspective are required to ensure that restorative justice practices do not undermine substantive justice or the protection of victims’ fundamental rights in sexual crime cases